The influence of a hip extension strengthening programme on gait performance in individuals following stroke - Busse, Monica (Department of Human Biology, 2017)
Gait difficulties experienced by individuals following a stroke may be related to the commonly observed reduced hip extension in the stance phase of gait. The aim of this initial exploratory study was to evaluate the effects of a home-based strengthening programme on hip muscle strength and gait performance in individuals following stroke. Six chronic stroke patients (> 9 months duration) participated in this pretest-posttest group design which was composed of two six week phases, A and B, where B immediately followed A. No training or advice was given to the six subjects during phase A. During Phase B, the same six subjects participated in a "hip extension focused" home exercise programme aimed at improving hip extensor muscle strength and the range of anterior hip structures. The exercise programme consisted of functional strengthening, task related activities and stretching. At the end of this sixweek period, the subjects were re-tested in order to evaluate the effects of the exercise programme. The outcome measures included isometric muscle strength, walking speed and range of the anterior structures of the hip. The walking section of the Motor Assessment Scale for Stroke and the Nottingham Extended Activities of Daily Living were also employed. In addition, clinical gait analysis was used to gather measures of gait velocity, step length and hip joint excursion. Statistically significant increases were found in the study group (n = 6) for the identified parameter of hip extensor strength after the intervention (p = 0.05), although this change could not necessarily be attributed to intervention effects alone. Hip extension strength was significantly correlated with (1) step length (r = 0.82; p = 0.04) and (2) joint excursion (r = 0.8; p = 0.05) after the intervention. These correlations, although tentative and not conclusive, suggest that hip extensor strength may influence gait performance and therefore warrants further investigation. While the results obtained from this exploratory study appear to suggest that the hip extensors play an important role in providing stability for the lower limb during gait, a randomised controlled study with a larger cohort of patients would be necessary to make any definitive conclusions.